2016
DOI: 10.5539/jfr.v5n3p55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blanching on Saponins and Nutritional Content of Moringa Leaves Extract

Abstract: Moringa <em>oleifera</em> leaves have been used as food material because it has high nutritional value. Many research have been conducted on moringa leaves extract as functional food and the additional material of nutrient for some food products (biscuit, bread, jelly drink), which it looked that adding moringa leaves extract above 5% decrease the consumer acceptance level toward the product because of the strongest unpleasant aroma and bitter taste, which is caused by saponins content in moringa l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 13 publications
(6 reference statements)
3
15
0
4
Order By: Relevance
“…The reduction by hot water blanching has also been observed by Indriasari and Kumalaningsih (2016), in moringa leaves and Nigerian vegetables by Temitope et al (2013). Indriasari and Kumalaningsih (2016) further assert that among 75, 85 and 95 °C, the best results were obtained at 85 °C. The authors opined that at a high temperature of blanching, enhanced osmosis occurs due to softened tissues, and saponins then decrease.…”
Section: Resultssupporting
confidence: 53%
“…The reduction by hot water blanching has also been observed by Indriasari and Kumalaningsih (2016), in moringa leaves and Nigerian vegetables by Temitope et al (2013). Indriasari and Kumalaningsih (2016) further assert that among 75, 85 and 95 °C, the best results were obtained at 85 °C. The authors opined that at a high temperature of blanching, enhanced osmosis occurs due to softened tissues, and saponins then decrease.…”
Section: Resultssupporting
confidence: 53%
“…Proses perendaman dalam larutan NaCl dan NaHCO3 dapat menurunkan rasa pahit pada Momordica charantia dan Lupinus albus (Rashima et al 2017b;Ertas dan Bilgicli 2014). Indriasari et al (2016) menyatakan dengan perebusan 85°C selama 7,5 menit mampu menurunkan kom-ponen saponin yang ada dalam daun kelor hingga 3,9%.…”
Section: Pendahuluanunclassified
“…The first step in this study was to reduce saponin levels using the blanching process, where as many as 100 g of Moringa leaves were blanched in 600 ml of water with temperature and processing time according to the treatment. To prevent a significant reduction in nutrients due to this process, the treatment temperature used was below 100 ˚C with no more than 7.5 minutes (according to the study conducted by of Indriasari et al, 2016). In addition, the addition of Moringa leaves into water is done when the temperature reached the treatment temperature to minimize contact between Moringa leaves and hot water.…”
Section: Blanching Processmentioning
confidence: 99%
“…The reduction in protein content due to the blanching process in this study was also shown by several other studies (Hefnawy., 2011;Mutiara et al, 2013;Nkafamiya et al, 2010;Mephba et al, 2007;Indriasari et al, 2016).…”
Section: Nutrition Levelsmentioning
confidence: 99%